Getting connected while aging: the effects of WeChat network characteristics on the well-being of Chinese mature adults. Issue 1 (2nd January 2019) - Rui, Jian Raymond; Yu, Nan; Xu, Qian; Cui, Xi
Abstract : We Chat is one of the most popular social media applications, ranking fifth globally. Drawing on the socioemotional selectivity theory, this study investigated the usage of WeChat among Chinese aged 50–80 years in 68 cities across the country. This study is the first to examine the effects of the characteristics of the WeChat network on users' psychological well-being (PWB) and subjective well-being (SWB). The results of the online survey (N = 506) suggested that making strong connections on WeChat positively affected the participants' PWB and SWB. Connecting with individuals who shared the same interests also improved the participants' PWB and SWB. However, connections with neighbors on WeChat decreased their PWB. Our findings have valuable implications for social networking platform designers, social workers, and the community of both emerging seniors and senior citizens.